2004
DOI: 10.1038/sj.jp.7211067
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of Prematurity and Pulse Oximetry: A National Survey of Recent Practices

Abstract: NICUs in the US today have a wide range of SpO2 guidelines. The results of this survey show a "gradient of risk" towards less retinal ablation surgery when the max SpO2 is <98% in the first 2 weeks following birth (p<0.05). There was a statistically significant lower rate of > or =stage 3 ROP and retinal ablation surgery when the max SpO2 was < or =92% after the first 2 weeks of age. A randomized, controlled trial is needed to establish a safe upper limit of SpO2 in the premature infant at risk for developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 26 publications
(18 reference statements)
3
96
2
3
Order By: Relevance
“…Although the precise oxygen saturations to avoid remain unknown, avoiding hyperoxia, and particularly avoiding swings between hyperoxia and hypoxia, in the first few weeks of life has been shown to decrease the severity of ROP Askie and Henderson-Smart, 2000;Tin et al, 2001;Chow et al, 2003;Anderson et al, 2004;York et al, 2004). The relationship between hyperoxia and subsequent neovascularization appears more complex than suggested previously.…”
Section: Implications For Prevention and Treatment Of Ropmentioning
confidence: 97%
“…Although the precise oxygen saturations to avoid remain unknown, avoiding hyperoxia, and particularly avoiding swings between hyperoxia and hypoxia, in the first few weeks of life has been shown to decrease the severity of ROP Askie and Henderson-Smart, 2000;Tin et al, 2001;Chow et al, 2003;Anderson et al, 2004;York et al, 2004). The relationship between hyperoxia and subsequent neovascularization appears more complex than suggested previously.…”
Section: Implications For Prevention and Treatment Of Ropmentioning
confidence: 97%
“…However, both the BOOST trial 13 and the STOP-ROP trial 16 showed detrimental effects in children randomized to high-vs. low-saturation regimes around gestational age 30 to 32 weeks and until close to term.…”
Section: Phasementioning
confidence: 99%
“…Several recent studies have shown a relationship between a high-oxygen saturation and ROP. [11][12][13][14] It seems that a SaO 2 >93% increases the risk for severe ROP and need for therapy. Furthermore, these studies also demonstrated more lung problems, including chronic lung disease, in infants nursed in a high-oxygen saturation.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease the risk of ROP, many neonatal intensive care units (NICUs) targeted lower SpO 2 in premature neonates receiving supplemental oxygen (12). Large randomized trials showed a reduction in severe ROP among survivors but increased mortality before discharge in extremely preterm infants when SpO 2 target was limited to 85-89% as compared to 91-95% from birth to 36 wk PMA (13,14).…”
mentioning
confidence: 99%